Quantifying Wedge‐Ice Volumes in Yedoma and Thermokarst Basin Deposits. (4th June 2014) - Ulrich, Mathias; Grosse, Guido; Strauss, Jens; Schirrmeister, Lutz
ABSTRACT Wedge‐ice volume (WIV) is a key factor in assessing the response of ice‐rich permafrost landscapes to thaw and in quantifying deep permafrost soil carbon inventories. Here, we present a method for calculating WIV in late Pleistocene Yedoma deposits and Holocene thermokarst basin deposits at four study areas in Siberia and Alaska. Ice‐wedge polygons and thermokarst mound (baydzherakh) patterns were mapped on different landscape units using very high‐resolution (0.5 m/pixel) satellite imagery (WorldView‐1 and GeoEye‐1). In a geographic information system (GIS) environment, Thiessen polygons were automatically created to reconstruct relict ice‐wedge polygonal networks, and field and published data on ice‐wedge dimensions were used to generate three‐dimensional subsurface models that distinguish between epi‐ and syngenetic ice‐wedge geometry. The results reveal significant variations in WIV between the study sites and within certain terrain units. Calculated maximum WIV ranges from 31.4 to 63.2 vol% for Yedoma deposits and from 6.6 to 13.2 vol% for thermokarst basin deposits. Copyright © 2014 John Wiley & Sons, Ltd.